Victim impact statement and lay judges’ decision making: exploring cross-cultural and individual differences in East Asia - Huang, Kuan-Ju (Psychology, crime & law, 2024)
Research has shown that emotional testimony given by victims or their family can affect jurors’ or lay judges’ decision-making processes, but little attention has been paid to cross-cultural and individual variations. The present study examined whether cultural and individual differences were associated with how victim impact statement (VIS) affected mock lay judges’ decision making in East Asian contexts. Participants from Japan (n = 74) and Taiwan (n = 64) reviewed a transcript of a lay participation (or Saiban-In) trial with or without an emotional VIS by the bereaved family and then made verdict and sentencing decisions individually. The results showed no main and interaction effects of VIS and culture on verdict decision, perceived strength of evidence, and sentence decision. Regression analyses showed that Need for Affect predicted higher perceived strength of evidence against the defendant and more guilty verdicts, and the effects were stronger in the VIS condition. We concluded that emotional VIS in a written format may not be biasing by nature in East Asian contexts; however, including a VIS could risk the possibility of bias in the fact-finding process of lay judges with a higher tendency to approach emotional information.